Advances in tourism behavior & retailing introduction to a special issue in Journal of Global Scholars of Marketing Science (JGSMS). Issue 1 (2nd January 2022) - Chen, Po-Ju; Ren, Lianping; Li, Xiangping; Yang, Fiona X.
ABSTRACT: This introduction reviews current issues in tourist behaviors and retailing. The article furthers the retailing shopping framework and its application to consumer behavior in general and tourism and retailing in particular. A summary of each of the six articles that follow appears. The article extends a note of appreciation to the members of the special editorial board for this issue.